Antibiotic and antitussive prescribing among urgent care and emergency department visits for respiratory diagnoses in a large health system. Issue 3 (30th May 2022) - Zakharevich, Marina; Kippenhan, Matthew A.; Lu, Alice; Courtney, D. Mark; McCarthy, Danielle M.; Kim, Howard S.
Abstract: Objective: Urgent care centers (UCs) commonly evaluate patients with respiratory infections, and patients increasingly prefer UCs to emergency departments (EDs) because of their customer‐centric approach. The aim of this study is to describe antibiotic and opioid prescribing among UC and ED visits with respiratory diagnoses. Methods: This is a cross‐sectional study of visits to 7 EDs and 6 UCs in the greater Chicago area. We included visits from July 1, 2017, to June 30, 2019, with a primary diagnosis of upper or lower respiratory infection. We describe the proportion of visits resulting in an antibiotic or antitussive prescription as well as the most frequently prescribed medications in these categories. We also describe the demographic and clinical characteristics of visits. Results: Of 9134 ED visits, 32.9% were prescribed an antibiotic and 14.4% an antitussive (6.6% opioid). Of 41, 380 UC visits for respiratory diagnoses, 57.9% were prescribed an antibiotic and 25.0% an antitussive (9.3% opioid). The most frequently prescribed antibiotics among ED and UC visits were penicillins (36.6% and 44.5%, respectively) and macrolides (44.1% and 35.3%, respectively). The most commonly prescribed opioid was codeine (55.6% and 91.0%, respectively). Median waiting room time was 16 and 5 minutes for ED and UC visits, respectively; median length of stay was 178 and 41 minutes, respectively. Conclusions: Antibiotics and antitussives, including opioids, are frequently prescribed for ED and UC visits with non‐bacterial respiratory diagnoses. These findings suggest greater attention to the appropriateness of antibiotic prescribing in both settings and the incorporation of specific guidance on codeine products in opioid‐prescribing guidelines.